Supply Chain Profitability Analysis and Development Strategy for Cinnamon Commodities in Jambi Province, Indonesia - Chatra, Afdhal; Rosi, Ade Irma (Agro Bali : Agricultural Journal, 2025)
Cinnamon is a leading commodity in Jambi Province and one of Indonesia's primary export commodities. However, the potential of this commodity is not entirely optimal. Many products are marketed in raw form, which limits added value and competitiveness. This study aims to analyze the added value produced by each member of the cinnamon supply chain and formulate a strategy for developing this commodity in Jambi Province. The informants to find out the added value of cinnamon in this study amounted to 105 people who were selected purposively. The number of informants to formulate a strategy for developing cinnamon commodities in Jambi Province is five people who are considered experts. Qualitative analysis was collected through surveys, in-depth interviews, observations, and document analysis. In contrast, quantitative analysis included the calculation of profitability ratios to assess added value at each stage of the supply chain, as well as IFE and EFE matrix analysis to identify internal and external factors that affect the competitiveness of Jambi cinnamon.  The study results show that farmers who sort products get higher profits than those who sell in raw form. Traders and exporters derive the most tremendous nominal gains due to economies of scale. The recommended strategies for developing cinnamon commodities in Jambi Province include increasing production capacity, diversifying products, government support, and improving infrastructure to increase the competitiveness of Jambi cinnamon in the global market.